The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1042/0264-6021:3440145
|View full text |Cite
|
Sign up to set email alerts
|

DNA-binding activity of the transcription factor upstream stimulatory factor 1 (USF-1) is regulated by cyclin-dependent phosphorylation

Abstract: The ubiquitous transcription factor upstream stimulatory factor (USF) 1 is a member of the bzHLH (leucine zipper-basic-helix-loop-helix) family, which is structurally related to the Myc family of proteins. It plays a role in the regulation of many genes, including the cyclin B1 gene, which is active during the G2/M and M phases of the cell cycle and may also play a role in the regulation of cellular proliferation. We show that the affinity of recombinant USF-1 for DNA is greatly increased by treatment with act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…The USF family is composed of the products of two ubiquitously expressed genes, USF1 and USF2, which can form homo-and heterodimers [48][49][50][51][52]. In general, the USF proteins activate genes that are involved in cellular differentiation in both developing and adult tissues [45,46,[53][54][55][56]. It was recently reported that USF2 is developmentally regulated in fetal rabbit lung, where it plays a key role in inducing the expression of pulmonary surfactant protein A [57].…”
Section: Discussionmentioning
confidence: 99%
“…The USF family is composed of the products of two ubiquitously expressed genes, USF1 and USF2, which can form homo-and heterodimers [48][49][50][51][52]. In general, the USF proteins activate genes that are involved in cellular differentiation in both developing and adult tissues [45,46,[53][54][55][56]. It was recently reported that USF2 is developmentally regulated in fetal rabbit lung, where it plays a key role in inducing the expression of pulmonary surfactant protein A [57].…”
Section: Discussionmentioning
confidence: 99%
“…This decrease in binding activity occurred in spite of T4-mediated increases in Usf1 mRNA levels 11 days after birth. It is possible that the small increase in Usf1 mRNA levels observed after T4 stimulation may be negated by other factors that inhibit USF1 DNA-binding activity by a posttranslational mechanism [58][59][60][61]. The exact mechanism of how thyroid hormone contributes to changes in USF activity during the transition from proliferation to differentiation within Sertoli cells remains to be determined.…”
mentioning
confidence: 88%
“…Thus, it was the aim of the present study to investigate whether USF-2 may also have a crucial role for rat HO-1 expression in either an inducible or a repressive manner. Because interspecies differences in the regulation of HO-1 gene expression in human and rat cells (30), as well as cell type-specific differences in the function of USF (11,15,47) were reported, we used rat primary hepatocytes (PHCs), rat hepatoma H4IIE cells, human primary pulmonary artery smooth muscle cells (PASMCs), human hepatoma HepG2 cells, and human HeLa cells in the present study.…”
Section: Introductionmentioning
confidence: 99%